Psychometric Properties of the GAD-7, GAD-2, and GAD-Mini in Peruvian College Students - Franco-Jimenez, Rulman Andrei (2022)
The psychometric properties of the General Anxiety Disorder-7 (GAD-7) and its ultra-short versions, the GAD-2 and the GAD-Mini, were evaluated in a sample of 407 students from two Peruvian universities (259 females and 148 males). First, a structural analysis was performed using the CFA, showing a good fit with respect to the instrument's unifactorial model χ²(14) = 31.717, CFI = .995, TLI = .992, RMSEA = .056, SRMR = .026. In addition, a measurement invariance analysis was performed, finding a stable unifactorial structure considering sex. Furthermore, evidence of convergent validity was analyzed in the GAD-7 and its ultra-short versions, presenting moderate correlations with instruments such as the PHQ-2 and the AAQ-II. The internal consistency of the instruments was evaluated using the omega coefficient and obtained high values of .89, .80, and .79 in the GAD-7, GAD-2, and GAD-Mini respectively. Therefore, it is concluded that the GAD-7 is a unifactorial instrument, invariant according to sex, with adequate internal consistency and convergent validity as well as its ultra-short versions in the sample studied.